The effect of ischaemic preconditioning on central and peripheral fatiguing mechanisms in humans following sustained maximal isometric exercise - Halley, S. L.; Marshall, P.; Siegler, J. C. (Experimental Physiology, 2018)
New findings: What is the central question of this study? Does ischemic preconditioning (IPC) influence central and peripheral fatiguing mechanisms during sustained maximal isometric exercise? What is the main finding and its importance? Voluntary activation and pre- to post-exercise reductions in resting twitch torque values were unchanged by IPC. However, an effect on tissue oxygenation was observed within the IPC trials where greater concentrations of deoxyhaemoglobin were recorded with concurrent upward trends of total haemoglobin concentrations. Employing a direct assessment of neural drive, this study found that IPC had no influence on either central or peripheral fatiguing pathways following maximal isometric exercise. Abstract: Ischemic preconditioning (IPC) is thought to inhibit neural feedback from metabolically sensitive muscle afferents during exercise. It was hypothesized that IPC could affect the mechanism of centrally mediated fatigue following a maximally fatiguing protocol. Eleven resistance trained males completed three 2 min maximal voluntary contractions (MVC's) via an isometric leg extension preceded by treatments of IPC (3 × 5 min bilateral leg occlusions at 220 mmHg), SHAM (3 × 5 min at 20 mmHg) or CON (30 min passive rest). Femoral nerve stimulation was utilised to explore central and peripheral fatigue pathways. This was profiled at baseline (BL), prior to the 2 min MVC (Pre), and then 10 s post (Post). Tissue oxygenation was measured throughout the 2 min MVC's via near-infrared spectroscopy. Pre to Post MVC and twitch torque levels declined (-71 ± 56; d = 1.33 ± 0.51, p < 0.007) (-51 ± 20 Nm; d = 3.76 ± 0.84, p < 0.005) respectively without differences between conditions (MVC; p = 0.67, twitch torque, p = 0.39). Voluntary activation was also unaffected by condition (p = 0.8). Peak deoxyhaemoglobin concentrations were elevated (3.7 ± 3.0 µmol-L ; d = 1.02 ± 0.46, p = 0.003) (3.0 ± 3.7 µmol-L ; d = 0.82 ± 0.57, p = 0.03) in the IPC trials relative to CON and SHAM respectively. These findings demonstrate that IPC does not affect central or peripherally mediated mechanisms of fatigue during a sustained 2 min maximal effort isometric leg extension task.